ATOPIC MARCH - Fetria Faisal; Hiddayaturrahmi Hiddayaturrahmi (Yayasan Nusantara Hasana Berdikari, 2026)
Atopic March refers to the natural progression of allergic diseases that commonly begins in early childhood and develops sequentially into other atopic conditions later in life. The condition typically starts with atopic dermatitis in infancy, followed by food allergies, allergic rhinitis, and asthma during childhood. The pathogenesis of atopic march involves a complex interaction between genetic predisposition, immune dysregulation, environmental exposure, and skin barrier dysfunction. Impaired skin integrity facilitates allergen sensitization, leading to chronic inflammatory responses mediated predominantly by immunoglobulin E (IgE). Clinical manifestations vary depending on the stage of disease progression and may significantly affect the quality of life of affected individuals. Diagnosis is based on clinical history, physical examination, and allergy testing when indicated. Management focuses on early identification, avoidance of triggering allergens, skin barrier protection, pharmacological therapy, and patient education to prevent disease progression and reduce complications. Early intervention is essential to improve long-term outcomes and minimize the burden of allergic diseases.